Shear Strength Behavior of Sand Reinforced by Kraft Paper Using the Ring Shear Apparatus - Wan-li Xie; Qianyi Guo; Nelson N.S. Chou; Rongsen Zhu; Maosheng Zhang (Advances in Civil Engineering)
To explore the reinforcement effects of different reinforcement methods, kraft paper was used as reinforcement material, and shear tests were carried out in sand to study the reinforcement effects of kraft paper perpendicular and parallel to the shear plane. The test results show that the two reinforcement methods can effectively improve the strength of sand and the orthogonal reinforcement form is more superior. The existence of reinforced materials greatly improves the cohesion of sand, but does not significantly improve the internal friction angle. The width of reinforcement material has little effect on the reinforcement effect and shows different variation laws under different reinforcement forms.